Veress needle insertion in the left hypochondrium in creation of the pneumoperitoneum - Azevedo,Otávio Cansanção de (2006)
PURPOSE: To test the efficacy of the puncture in the left hypochondrium as an alternative method. METHODS: Sixty-two patients randomly distributed into two groups were studied: Group LH, puncture in the left hypochondrium (n=30), and Group ML, puncture in the abdominal midline (n=32). The following were assessed: needle positioning tests, number of failed attempts at needle insertion, and time needed for creation of pneumoperitoneum. Gas flow, volume and intraperitoneal pressure were recorded at every 20 seconds, until a 12 mmHg pressure was reached inside the peritoneal cavity. RESULTS: A similar number of positive results for the needle positioning tests were observed in both groups. Two failed attempts to reach the peritoneal cavity were observed in Group ML and one in Group LH. The time necessary for the creation of pneumoperitoneum was on average 3 minutes and 46 seconds for Group LH, and 4 minutes and 2 seconds for Group ML. Average gas flow, volume and pressure were equivalent for both groups. CONCLUSION: Puncture in the left hypochondrium was as effective as puncture in the abdominal midline for the creation of pneumoperitoneum.